Nutraceutical Profile of "Carosello" (Cucumis melo L.) Grown in an Out-of-Season Cycle under LEDs - Onofrio Davide Palmitessa; Miriana Durante; Annalisa Somma; Giovanni Mita; Massimiliano D'Imperio; Francesco Serio; Pietro Santamaria (MDPI AG, 2022)
The world population is projected to increase to 9.9 billion by 2050 and, to ensure food security and quality, agriculture must sustainably multiply production, increase the nutritional value of fruit and vegetables, and preserve genetic variability. In this work, an Apulian landrace of Cucumis melo L. called "Carosello leccese" was grown in a greenhouse with a soilless technique under light-emitting diodes (LEDs) used as supplementary light system. The obtained results showed that "Carosello leccese" contains up to 71.0 mg·g−1 dried weight (DW) of potassium and several bioactive compounds important for human health such as methyl gallate (35.58 µg·g−1 DW), α-tocopherol (10.12 µg·g−1 DW), and β-carotene (up to 9.29 µg·g−1 DW under LEDs). In fact, methyl gallate has antioxidative and antiviral effects in vitro and in vivo, tocopherols are well recognized for their effective inhibition of lipid oxidation in foods and biological systems and carotenoids are known to be very efficient physical and chemical quenchers of singlet oxygen. Finally, it was demonstrated that the LEDs' supplementary light did not negatively influence the biochemical profile of the peponids, confirming that it can be considered a valid technique to enhance horticultural production without reducing the content of the bioactive compounds of the fruits.